2019
DOI: 10.1007/s42452-019-1473-5
|View full text |Cite
|
Sign up to set email alerts
|

Soret–Dufour and radiative aspects in hydromagnetized nanofluid flow in stratified porous medium

Abstract: The numerical computations of Soret-Dufour aspects in hydromagnetics nanofluid flow in thermal stratified porous medium under radiated chemical reaction are developed. The unique similarity transformations lead to reduce the partial differential system into expressions of ordinary ones. Keller-box approach is adopted to express the numeric solutions. The impacts of embedded flow parameters on the different flow profiles signifying velocity, concentration and temperature of nanofluid are discussed via graphs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The increment in Nusselt number is computed versus Le R Dr Sr , , , , and n. The comparative study is presented in Table1for the heat transfer rate. It is obvious that the obtained results are in excellent agreement with the findings reported in Reference[12].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The increment in Nusselt number is computed versus Le R Dr Sr , , , , and n. The comparative study is presented in Table1for the heat transfer rate. It is obvious that the obtained results are in excellent agreement with the findings reported in Reference[12].…”
supporting
confidence: 91%
“…With the use of similarity transformation, the nonlinear partial differential equations with subjected boundary conditions are converted into ordinary differential equations then solved by using the shooting method. Here, the third-order nonlinear ordinary differential equation (10) and second-order nonlinear ordinary differential equations ( 11) and (12) have been reduced to first-order differential equations as follows:…”
Section: Numerical Methods For Solutionmentioning
confidence: 99%
“…Murugesan et al 19,20 studied the influences of heat generation on MHD nanofluid with viscous dissipation. Unsteady Nanofluid flow 21 with variable properties and their influences on a stretched sheet was presented by Mjankwi. 22 It was observed that porosity and magnetic parameters have the ability to slower down the nanofluid velocity and enhancing the thermal and concentration profiles.…”
Section: Introductionmentioning
confidence: 99%
“…e purpose of the current study is to discuss the comparative impact of MHD flow [27][28][29][30] of Newtonian, Maxwell, Williamson, and Casson fluids under the effects of internal heat source/sink, thermal radiation, chemical reaction, and thermophoretic velocity [31][32][33][34][35][36] on the momentum and heat and mass transfer over a stretching sheet with permeability effects [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%